Find integers A and B, such that (5x +4)/((2-x)(1+3x)) = A/(2-x) + B/(1+3x)

Adding the fractions on the RHS of the equation in the usual way gives 

A/(2-x) + B/(1+3x) = (A(1+3X) +B(2-X))/((2-X)(1+3X)) = (5x +4)/((2-x)(1+3x)) 

This gives an expression for the original numerator in terms of A B and x. 

A(1+3X) +B(2-X)) = 5x +4

Take values of x which simplify the equation e.g x = 2, -1/3

Gives A = 2, B = 1

So (5x +4)/((2-x)(1+3x)) = 2/(2-x) + 1/(1+3x)

Answered by Lorne F. Maths tutor

5267 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Why can't you divide something by 0?


Use implicit differentiation to find dy/dx of: 2(x^2)y + 2x + 4y - cos((pi)y) = 17


Differentiate y= 2^x


June 2008 C1 Paper Differentiation Question


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences